Bacteriocins from Lactobacillus plantarum – production, genetic organization and mode of action: produção, organização genética e modo de ação - Todorov, Svetoslav D. (Sociedade Brasileira de Microbiologia, 2009)
Bacteriocins are biologically active proteins or protein complexes that display a bactericidal mode of action towards usually closely related species. Numerous strains of bacteriocin producing Lactobacillus plantarum have been isolated in the last two decades from different ecological niches including meat, fish, fruits, vegetables, and milk and cereal products. Several of these plantaricins have been characterized and the aminoacid sequence determined. Different aspects of the mode of action, fermentation optimization and genetic organization of the bacteriocin operon have been studied. However, numerous of bacteriocins produced by different Lactobacillus plantarum strains have not been fully characterized. In this article, a brief overview of the classification, genetics, characterization, including mode of action and production optimization for bacteriocins from Lactic Acid Bacteria in general, and where appropriate, with focus on bacteriocins produced by Lactobacillus plantarum, is presented.